Kinematics of side-foot ball stopping technique in soccer - lga, T.; Nunome, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The present study aimed to illustrate the kinematics of side-foot ball stopping in soccer. Eleven male university soccer players performed side-foot ball stops of an air ball fired from a machine from 10 m away. The ball stopping motion was captured using a 10-camera motion capture system sampling at 500 Hz. The changes of foot and ball linear velocities were computed just before, during and after ball contact. Six joint angular motions of the stopping leg were also calculated. The participants demonstrated a distinct draw back of the foot before ball contact after a gentle forward swing. A rapid knee external rotation was also initiated just after ball contacting, suggesting the knee was passively rotated externally. These kinematic aspects may represent significant motion features required for the side-foot ball stopping technique in soccer.